Penguatan Nilai Pancasila di Tengah Disrupsi Moral Generasi - Hendro Juwono (MOMENTUM : Jurnal Sosial dan Keagamaan, 2020)
Abstract recently, conflicts between fellow citizens but different beliefs have occurred, the conflict is viral on social media. First, residents in Bekasi play a song using a sound system when residents of other religions perform worship in one of the buildings. The two Mojokerto Regency Governments, Bangsal District, Ngastemi Village sent a letter to one of its residents named Sumarmi living in RT 03 Dusung Karangdami regarding the prohibition of installing all forms of crosses in his house and the prohibition of Christian worship activities which are usually held at Sumarni's residence. The letter was signed by the Village Head of Ngastemi Mustadi and had a wet stamp on the village office as of September 21, 2020. The incident in Bekasi and Mojokerto was part of environmental disruption, namely a fundamental change from the interaction process of a more mature democratic transition stage so that systematic-structured decisions and policies were needed. from stakeholders to create a more democratic and civilized Indonesia. The research method in the article uses a qualitative method with the type of literature. The results of this article's literacy discussion concluded that the role of the family, educational institutions, the environment in strengthening the values ​​of Pancasila is very large, especially when children have not entered 6 years, until adolescence, and parents. Strengthening the value of Pancasila from childhood to adolescence becomes a living asset for interacting with the environment, tolerance, help, and mutual respect, which is manifested in speech, attitude, behavior, and decisions taken.